Intergrated Criminal Policy: Peran Kementerian Agama Dalam Pencegahan Tindak Pidana Korupsi - Jusafri Jusafri (SASI, 2021)
This research aims to determine the relationship between criminal law policies as an effort to prevent corruption and to analyze how the Ministry of Religion program should be in preparing programs for preventing corruption in relation to the Integrated Criminal Policy. So that the writing will discuss the relationship between criminal law policies as an effort to prevent corruption and an integrated criminal law policy or Integrated Criminal Policy can increase the role of the Ministry of Religion in preventing corruption. The approach used in this research is the statute approach to examine regulations related to the Ministry of Religion and the prevention of corruption, the conceptual approach, which is to move from the views and doctrines in criminal law related to criminal law policies. integrated (integrated criminal policy). Prevention of corruption which is explicitly stated in UNCAC, the KPK Law and the United Nations Convention on crime prevention is an effort outside of criminal law (non-penal) which is an inseparable part of criminal law policy. The social policy carried out by the Ministry of Religion in preventing corruption is an effort outside of criminal law (non-penal) and can balance the eradication of corruption through criminal law (penal) carried out by law enforcers. This kind of social policy is a manifestation of an integrated criminal law policy that can be carried out by the government.